Identification of Potential F Populations from Intraspecific Crosses in Upland Cotton: F2 Progenies of Cotton - Baloch, Muhammad Jurial; Kakar, Muhammad Sharif; Jatoi, Wajid Ali; Veesar, Nasreen Fatima (Biological Sciences - PJSIR, 2010)
Ten intraspecific F2 progenies alongwith their six parental lines were evaluated for genetic parameters. The mean performance of genotypes differed significantly for various traits. Further, among F2 progenies, NB-111/S ´ CIM-499 expressed maximum heritability percentage coupled with high genetic variance and more genetic gains for days to open first flower and plant height, whereas CIM-497 ´ CIM-506 exhibited higher heritability percentage, associated with more genetic variance, consequently higher genetic gains for boll weight and seed cotton yield. Progeny NB-111/S ´ CIM-506 exhibited moderate heritability percentage paired with fair amount of genetic variance and appreciable genetic gains for number of sympodia per plant. For number of bolls and lint percentage, progeny BH-147 ´ CIM-499 expressed maximum heritability percentage coupled with high genetic variance and greater genetic gains. Nevertheless, progeny B.T. cotton ´ CIM-499 displayed higher heritability percentage, paired with more genetic variance and greater genetic gains for fibre length and also expressed maximum values for all the other traits except plant height, boll weight and G.O.T%. As a whole, quite a number of F2 progenies expressed moderate to high heritability estimates, fair amount of genetic variance and sufficient amount of predicted genetic gains, suggesting reliability of such breeding material for use as potential segregating populations for screening desirable segregants from subsequent generations of selfing for improvement of most of the traits studied.